Myrmecofauna in eucalyptus plantations in the Mário Xavier National Forest, Rio de Janeiro State, Brazil - Ana Paula Neves de Azevedo; Fábio Souto Almeida (Floresta e Ambiente)
Abstract This study aimed to analyze the taxonomic and functional diversity of the ant fauna in eucalyptus plantations (Corymbia citriodora; Eucalyptus urophylla; and E. saligna) in the Mário Xavier National Forest, state of Rio de Janeiro, Brazil. The E. saligna plantation was adjacent to an urban area, while the others were at least 1 km away. A total of 36 ant species from 14 genera were collected. The largest number of species was found in the C. citriodora plantation (20), followed by E. urophylla (18) and E. saligna (9) plantations. Species composition varied significantly among the areas. Greater numbers of guilds were found in the C. citriodora and E. urophylla plantations (6) compared to the E. saligna plantation (4). These results indicate that environmental attributes and proximity to urban areas can affect the richness and composition of ant species in eucalyptus plantations, consequently influencing the functional diversity.